Strategi Komunikasi Marketing Public Relations Barli Coffee - Agung Priyono; Dadi Ahmadi (Jurnal Riset Public Relations, 2021)
Abstract. Barli Coffee, one of the Coffee Shops in the city of Bandung, which is adjacent to the Art Museum, has a different concept from other Coffee Shop concepts. Entering the era of globalization, competition in various fields is getting real. The success of the performance of Public Relations as an important item of the organization or company tasked with creating and maintaining a positive value or image of the organization is getting higher. When viewed from the marketing mix carried out by Barli Coffee, there are several marketing mixes that are applied to the marketing strategy process at Barli Coffee, namely the initial marketing strategy, which was carried out in the first month by Barli, namely doing live music. The second marketing strategy, which Barli Coffee Shop does is to carry the concept of "Friday I'm In Love" this concept intends to hold a promo every Friday. The "Friday I'm In Love" promo was established since the PSBB was tightened and the concept of the promo is that every consumer who comes can pay sincerely. The third marketing strategy carried out by activities that can be carried out at Barli Coffee is such as podcasts and live concerts. The researcher wanted to find out more about Barli Coffee's marketing public relations communication strategy regarding the promotion of "Friday I'm In Love". The aim is to find out the process of marketing public relations communication strategy, the obstacles that occur during the marketing public relations communication strategy process, and the reasons why choosing social media as a promotional medium. The research methodology is a qualitative-descriptive method with a single holistic case study research approach. Data collection techniques are carried out by interview, observation, documentation, and literature study. The research subjects of key informants consist of internal parts sales & marketing, and barista Barli Coffee and supporting informants, owner of Barli Coffee. The result of the research is that the pull strategy applies tactics to promote "Friday I'm In Love" the tactic used is to hold the promotion every Friday. By holding this promo, which is to offer added value to consumers, as a stimulus to maximize sales. One of which is undertaken by Barli, namely by collaborating with several companies or brands. The obstacles are the lack of a graphic design team to focus on work on social media content and operating hours which have the effect of reducing the entry of Barli and this Health Protocol affecting places that are not allowed to be occupied due to regulations from the Government. The reason for using Instagram is because it can attract consumers widely, follow trends, and get positive feedback. Abstrak. Barli Coffee salah satukCoffee Shop diokota Bandung yang berdampingan dengan Museum art ini memiliki konsep yang berbeda dengan konsep-konsep Coffee Shop lainnya. Memasuki era globalisasi, persaingan di berbagai bidang semakin nyata saja. Keberhasilan kinerja Public Relations sebagai item penting organisasi atau perusahaan yang bertugas menciptakan dan mempertahankan nilai atau image positif organisasi semakin tinggi. Jika dilihat dari bauran pemasaran yang dilakukan Barli Coffee ada beberapa bauran pemasaran yang diaplikasikan pada proses strategi marketing di Barli Coffee yaitu Strategi marketing awal, yang dilakukan di bulan pertama oleh Barli yaitu melakukan live music. Strategi marketing kedua, yang Barli Coffee Shop lakukan adalah mengusung konsep “Friday I’m In Love” konsep ini bermaksud mengadakan promo di setiap hari Jum’at. Promo “Friday I’m In Love” didirikan semenjak PSBB diperketat dan konsep dari promo tersebut yaitu setiap konsumen yang datang dapat membayar se-Ikhlasnya. Strategi marketing ketiga yang dilakukan kegiatan yang dapat dilakukan di Barli Coffee yaitu seperti Podcast, dan live concert. Peneliti ingin mengetahui lebih lanjut strategi komunikasi marketing public relations Barli Coffee mengenai promosi “Friday I’m In Love”. Tujuannya untuk mengetahui proses strategi komunikasi marketing public relations, hambatan-hambatan yang terjadi selama proses strategi komunikasi marketing public relations itu terjadi, dan alasannya kenapa memilih media sosial sebagai media promosi. Metodologi penelitiannya yaitu metode kualitatif-deskriptif dengan pendekatan penelitian studi kasus tunggal holistic. Teknik pengumpulan data yang dilakukan dengan wawancara, observasi, dokumentasi, dan studi pustaka. Subjek penelitian pada key informant terdiri bagian internal yaitu sales & marketing, dan barista Barli Coffe serta informan pendukungnya yaitu owner Barli Coffee. Hasil penelitiannya yaitu penerapan taktik untuk mempromosikan “Friday I’m In Love” dengan mengadakan promosinya pada setiap hari Jum’at. Dengan diadakan promo ini yaitu menawarkan nilai tambah kepada konsumen, sebagai suatu stimulus untuk mendorong penjualan dengan maksimal. Kemudian salah satu yang dijalani oleh Barli yitu dengan berkolaborasi dengan beberapa perusahaan atau brand. Hambatannya yaitu kurangnya tim design grafis untuk fokus kerja di konten media sosial dan jam operasional yang dampaknya mengurangi pemasukkan Barli dan Protokol Kesehatan ini mempengaruhi tempat-tempat yang tidak boleh ditempati karena adanya aturan dari Pemerintah. Alasan menggunakan media sosial Instagram karena dapat menarik konsumen secara luas, mengikuti trend, dan mendapatkan feedback positif.